Perishable Inventory Control Model for Food Production in Pizza Restaurant - Ahznizam, Nur Syahirah; Muhammad Basri, Cik Sri Mazzura (Enhanced Knowledge in Sciences and Technology, 2024)
Inventory management plays the most important role in every business to ensure a smooth production process and fulfillment of customers’ demands. A failure to control the inventory will result in increased inventory costs and shortage costs. In a pizza restaurant, too much inventory of perishable items in one period will cause damaged items due to their shelf life. Thus, this study explores the critical task of inventory management in a pizza restaurant in order to achieve minimum total cost. This study focuses on the development of an inventory control model designed to minimize item costs while ensuring adequate stock levels and no wastage. Key factors considered in this model include the cost of purchasing per unit, holding costs, and ordering costs, along with other factors such as lead time and inventory shelf life. Through practical testing, the model reveals the optimum storage times for the items and leads to the identification of the optimum quantity of the items that should be ordered in each order. The finding shows that the implementation of this model has the potential to significantly increase the profit by reducing the overall inventory expenses. Despite the study’s limitations, such as constant demand, the results show that the proposed inventory control model improves accuracy and successfully reduces the total inventory costs. So, this study provides valuable insights for restaurant managers to manage inventory efficiently and ultimately contribute to improved financial performance and sustainability in the industry.